2018
DOI: 10.1111/and.13086
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects ofArctium lappaL. Extract on testicular injuries induced by ethanol in rats

Abstract: The aim of this study is to assess the antioxidant activity and also protective effects of Arctium lappa L. (AL) extract on ethanol-induced testicular injuries in rats. In addition, the total phenol and flavonoid contents of the methanolic extracts were analysed and the antioxidant activity of the extract was investigated. The studied extract possessed strong antioxidant activity (IC ; 0.113 ± 0.007 mg/ml) and exhibited more active than the ascorbic acid (IC ; 0.142 ± 0.002 mg/ml). The histological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
2
12
2
Order By: Relevance
“…Indeed, our result showed no difference in epididymal sperm concentration as compared between control and ethanol-treated animals for 14 consecutive days as shown in Table 1. In contrast, it was totally different from a previous study reported by Yari et al (2018) showing sig- to early affect spermatogenesis because some seminiferous epithelium obviously showed some histopathologies (Figure 4) with reduction of serum testosterone levels (Table 1). These results are also similar to those investigations previously observed by Yari et al (2018).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Indeed, our result showed no difference in epididymal sperm concentration as compared between control and ethanol-treated animals for 14 consecutive days as shown in Table 1. In contrast, it was totally different from a previous study reported by Yari et al (2018) showing sig- to early affect spermatogenesis because some seminiferous epithelium obviously showed some histopathologies (Figure 4) with reduction of serum testosterone levels (Table 1). These results are also similar to those investigations previously observed by Yari et al (2018).…”
Section: Discussioncontrasting
confidence: 95%
“…Indeed, it has been demonstrated that ethanol treatment in long period could decrease sperm amount in adult rats (Nishi et al, 2018;Yari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples airdried and grounded were at room temperature without sunlight. The extract was prepared according to the method used by Yari et al (2018). The dried leaves (25 g) were extracted twice for 72 h in 1 L of ethanol 70% (v/v) using the Soxhlet apparatus.…”
Section: Preparation Of Hydroethanolic Extract From Slmentioning
confidence: 99%
“…AL L. possessed strong antioxidant activity (IC 50 ; 0.113±0.007 mg/ml) and exhibited more active than the ascorbic acid (IC 50 ; 0.142±0.002 mg/ml). The histological examinations revealed that the coadministration of ethanol and AL extract inhibits the testicular injuries, alterations in superoxide dismutase activity, and H 2 O 2 and malondialdehyde (MDA) levels were observed in ethanoltreated rats in comparison to the control group [50]. Treatment with the ethanol extract of AL L. roots improved working and reference memory in mice in the Y-maze and passive avoidance tests.…”
Section: Antioxidant Activitymentioning
confidence: 99%